(3GdagQSJ dRcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQi GdTGaYi Cd jMji GdeJhaj SfI (B926(3g`s - (3TeS GdOjf eMeO Hf YHO GdQMef GdSNGhis; (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gdg eGfM GdYdeGA dGSjeG HGdSfI GdhGVMI GdOdGFd adeG cGf ef NUGFU gPg GdSfI aQZH Edi LeGYI ef GdBNPjf Yfi GdYde ai LeY CTHGg eG GdMGLI eGSg Edjg s
(3BNQgG (B:s
(3bGd LGeYI TeS GdOjf eMeO Hf YHO GdQMef GdSNGhi GdTGaYi ZaQ Gddg dg gPG BNQ eG hbaJ Ydjg , hGdMeO ddg ChdkG hBNQkG , GfJgi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B383 - (3U(B453s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
Keywords: (3GdJGQjNs